Sex Differences in Nutrition, Growth, and Metabolism in Preterm Infants - Alur, Pradeep (Frontiers in Pediatrics, 2019)
Biological differences between the sexes are apparent even from the early part of the pregnancy. The crown-rump length is larger in male fetuses compared to females in the first trimester. Placentae of male and female fetuses have different protein and gene expressions, especially in adverse conditions. Even within the intrauterine milieu, the same extracellular micro RNA may show upregulation in females and downregulation in male fetuses. There appears to be a natural survival advantage for females. Maternal glucocorticoids (GC) play an important role in fetal growth and organ maturation. However, excess glucocorticoids can not only affect the growth but the response may be sex-specific and probably mediated through glucocorticoid receptors (GR) in the placenta. Mild pre-eclampsia and asthma are associated with normal growth pattern in males, but in female fetuses, they are associated with a slowing of growth rate without causing IUGR probably as an adaptive response for future adverse events. Thus, female fetuses survive while male fetuses exhibit IUGR, preterm delivery and even death in the face of another adverse event. It is thought that the maternal diet may not influence the growth but may influence the programming for adult disease. There is growing evidence that maternal pre-pregnancy overweight or obesity status is directly associated with a higher risk of obesity in a male child, but not in a female child, at one year of age. It is observed that exposure to gestational diabetes is a risk factor for childhood overweight in boys but not in girls. It is fascinating that male and female fetuses respond differently to the same intrauterine environment, and this suggests a fundamental biological variation most likely at the cellular and molecular level.